Indulgent Parenting and the Psychological Well-Being of Adolescents and Their Parents - Qinglan Feng; Ming Cui (MDPI AG, 2023)
Adolescence is a time for identity development and exploration. Indulgent parenting during adolescence could be developmentally inappropriate and could be associated with adolescent psychological well-being problems. Little research on indulgent parenting, however, has included and investigated both adolescent and parental well-being problems. To extend the literature, the current study used both adolescent and parental reports in a dyadic context to investigate the association between indulgent parenting and the psychological well-being problems of both adolescents and their parents. This study used a sample of 128 adolescent-parent dyads. The findings from the actor-partner interdependence model (APIM) suggested that (1) the adolescent perceptions of behavioral indulgent parenting were significantly related to their own well-being problems; (2) the parents' perceptions of relational and behavioral indulgent parenting were significantly related to their own well-being problems; and (3) no effects were found between adolescents and their parents. The findings from this study have implications for prevention and intervention programs to improve parenting practices and reduce parents' well-being problems.